Development of Quality Management in Increasing Company Competitiveness - Suwanda, Suwanda (Jurnal Info Sains : Informatika dan Sains, 2023)
Product quality and production processes are key factors in competing in an increasingly tight global market. This research aims to investigate and develop effective quality management strategies to increase company competitiveness. This research uses a descriptive qualitative approach. The research results show that the development of quality management plays a crucial role in increasing the competitiveness of manufacturing companies. Through the implementation of Total Quality Management (TQM), Six Sigma, and Lean Manufacturing, companies can increase efficiency, reduce waste, and improve product quality. Information technology integration, especially through Quality Management Systems (QMS), helps companies track, measure and improve quality performance more efficiently. Employee training is a key factor in ensuring understanding of quality standards and their role in achieving the company's quality goals. Additionally, the collection and analysis of quality data supports the identification of trends, root causes of problems, and more informed decision making.